Boosting sesame production through frontline demonstrations under rainfed conditions in Pali district of Rajasthan, India: BOOSTING SESAME PRODUCTION THROUGH FRONTLINE DEMONSTRATIONS IN RAJASTHAN - M L MEENA; DHEERAJ SINGH (Journal of Oilseeds Research, 2019)
Sesame is an important kharif oilseed crop of India. It occupies about 3.6 per cent of area and 10.8 per cent of production of the total oilseeds production in India. Frontline demonstrations on sesame variety RT 351 were conducted at farmers’ fields in district Pali, Rajasthan during kharif 2014-15 to 2018-19. The yield data indicated 36.7 per cent higher mean seed yield in demonstration plots as compared to farmers’ traditional practices. The extension gap, technology gap and technology index were 200 kg/ha, 330 kg/ha and 31.4 per cent, respectively. Additional investments of `1320/ha coupled with scientific monitoring of demonstrations and non-monetary factors resulted in additional returns of ` 9459/ha. Fluctuating MSP sale price of sesame during different years influenced the economic returns per unit area. The mean benefit cost ratio over the five year period was 2.1 in demonstration plots and 1.4 in farmers’ practice plots.